2014
DOI: 10.1021/nn5004088
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive Tubular Polymersomes: Formation and Applications in Cellular Delivery

Abstract: Optimizing the shape of a nanovector influences its interaction with a cell and determines the internalization kinetics. Block copolymer amphiphiles self-assemble into monodisperse structures in aqueous solutions and have been explored extensively as drug delivery vectors. However, the structure of self-assembled block copolymers has mainly been limited to spherical vesicles or spherical and worm-like micelles. Here we show the controlled formation and purification of tubular polymersomes, long cylindrical ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(130 citation statements)
references
References 65 publications
3
126
0
1
Order By: Relevance
“…12,13 In addition, the shape of these polymersomes can be transformed into a large array of morphologies. [14][15][16] In general, vesicles can change shape from an initially spherical morphology via two possible routes: deflation via oblates (discs) or deflation via prolates (rods) as is shown in Figure 1 In order to gain more information about the shape of the formed structures, dry and cryoelectron microscopy techniques, both in scanning (SEM) and transmission (TEM) mode, are the method of choice. 18 In some cases differentiation between different morphologies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, the shape of these polymersomes can be transformed into a large array of morphologies. [14][15][16] In general, vesicles can change shape from an initially spherical morphology via two possible routes: deflation via oblates (discs) or deflation via prolates (rods) as is shown in Figure 1 In order to gain more information about the shape of the formed structures, dry and cryoelectron microscopy techniques, both in scanning (SEM) and transmission (TEM) mode, are the method of choice. 18 In some cases differentiation between different morphologies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that spherical polymersomes, assembled from poly(ethylene glycol)-polystyrene (PEG-PS), deflate into cup-shaped polymersomes called stomatocytes232425. Rod-shaped polymersomes have been created by using crosslinkers26 or rehydration27. Bicontinuous cubic structures have been reported as well28.…”
mentioning
confidence: 99%
“…In particular, nanotubes (tubular polymersomes) are exciting candidates for the development of NVs due to their high aspect ratio and potential for immunotherapy, alongside drug delivery. Nanotubes have been engineered through chemical cross-linking using bio-orthogonal click chemistry [66] or polymer blending in a film rehydration process [67]. Recognising the importance of using biodegradable polymers in the design of materials for medical applications [68] we have recently developed a facile methodology for the generation of biodegradable nanotubes via the osmotically-induced elongation of PEG-polylactide polymersomes [69].…”
Section: Morphological Engineering Of Polymeric Nanostructuresmentioning
confidence: 99%